Answer:
an = 2 + n
Step-by-step explanation:
The differences between terms are all 1. The first term is 3. The general form of the general term is ...
an = a1 + d(n -1)
Filling in a1 = 3 and d = 1, we have ...
an = 3 + n - 1
an = 2 + n . . . . . . simplify
Answer:
2
Step-by-step explanation:
Each time you flip a coin, there is a 50% change of it landing on tails. So half the time you should get a tails.
Half of 4 is 2, so you will likely get 2 tails.
0 is the awnser —————-1————-
Answer:
I won't solve i'll translate like you asked
Step-by-step explanation:
13) x - 5 = 21
14) 12 × y = 48
15) b + 10 = 13
If you want I can solve.
HOPE THIS HELPED